Genetic Characterization and Breeding Habitats of Black Fly (Diptera, Simuliidae) Vector Species in Laos - Isara Thanee; Bhuvadol Gomontean; Waraporn Jumpato; San Namtaku; Komgrit Wongpakam; Wannachai Wannasingha; Khamla Inkhavilay; Banchai Malavong; Pairot Pramual (Diversity, 2024)
Genetic diversity and ecology are two important aspects of vector species crucial to a full understanding of disease epidemiology. In this study, we examined genetic diversity, genetic structure and the physiochemical parameters of the breeding habitats of the two significant black fly vector species, Simulium chumpornense Takaoka and Kuvangkadilok and S. nodosum Puri, from Laos. Genetic diversity of S. chumpornense in Laos was relatively high with maximum genetic divergence of 3.05% but no significant genetic differentiation between populations. Comparisons with conspecific populations from Thailand also found no genetic differentiation between the two countries. This possibly related to the recent history of this species, as a very recent (31,000 years ago) historical population expansion was detected. Physicochemical parameters of the breeding habitats suggest the ability to utilize diverse stream sizes from small flows (1 m wide) to huge rivers (290 m or more wide). Populations of S. nodosum from Laos had low genetic diversity with maximum genetic divergence of 2.56% and no genetic structuring among populations. Comparisons with those reported from other countries revealed five genetically divergent lineages (I–V) with minimum genetic divergence of 1.36%. The majority (42 of 52) of specimens from Laos belonged to lineage I and the remaining (10) comprised lineage II. Lineage I is the largest and representative of specimens from Thailand, Myanmar, Vietnam, Taiwan and Laos. Population history analysis revealed that lineage I had undergone recent demographic expansion dating back to 7000 years ago. This very recent population expansion resembles others reported from Thailand and possibly indicates a response to increasing human and domestic animals following the agricultural revolution. Breeding sites of S. nodosum are diverse in respect to elevation, velocity, water conductivity and streambed particle size. The ability to utilize a wide variety of breeding sites could promote the production of a large adult population, which can be a pest for humans and other animals.